PHOTOGRAMMETRIC TECHNIQUE FOR ANALYZING RAINDROP SIZE DISTRIBUTION - Samuel Law Lik, Ging; Kuok King, Kuok; Po Chan, Chiu; Md. Rezaur, Rahman; Muhamad Khusairy, Bakri; Mei Yun, Chin (JOURNAL OF SOUTHWEST JIAOTONG UNIVERSITY, 2022)
Rainfall erosivity and rainfall kinetic energy are predominantly affected by the rainfall droplet size distribution characteristics. This study aims to determine the raindrop size distribution with different rainfall intensities in East Malaysia using photographic method and MATLAB image processing tools. A total of five natural rainfall intensities of different ranges were analyzed: 5.51 mm hr-1 , 14.20 mm hr-1 , 28.80 mm hr-1 , 32.41 mm hr-1 and 58.11 mm hr-1 . A digital camera with fast capturing mode was used to capture falling raindrops and the droplets were then processed in MATLAB to determine the raindrop size distribution. It was found that the captured raindrop diameters were within the range of 0.1 mm and 5.0 mm, and a higher portion of the raindrops fell between 0.1 mm and 1.0 mm. The results also showed that higher rainfall intensities would promote the formation of larger raindrop sizes, i.e., from 1.0 mm to 5.0 mm, and lower rainfall intensities tended result in higher drop counts in smaller raindrop sizes of <1.0 mm. The modified image processing tools of MATLAB had proved a shorter analysis duration and higher accuracy of the raindrop size determination than the human visual system. The novelty of this study contributes to the understanding of the equatorial rainfall properties. This enhances the study of the rainfall kinetic energy and soil erosion rate estimation. The findings demonstrate the capability of photogrammetric techniques for determination of raindrop size distribution.